Synthetic Alkaloid Treatment Influences the Intestinal Epithelium and Mesenteric Adipose Transcriptome in Holstein Steers - McLean, Kyle J.; Baldwin, Ransom L.; Li, Cong-jun; Klotz, James L.; Edwards, J. Lannett; McLeod, Kyle R. (Frontiers in Veterinary Science, 2020)
Holstein steers (n = 16) were used to determine if a synthetic alkaloid, bromocriptine, would alter the transcriptome of the small intestine and adjacent mesenteric adipose. On d 0, steers were assigned to one of two treatments: control (CON; saline only) or bromocriptine (BROMO; 0.1 mg/kg BW bromocriptine mesylate injected intramuscularly every 3 d for 30 d). Steers were slaughtered and midpoint sections of jejunal epithelium and associated mesenteric fat were collected for RNA isolation. Transcriptome analysis was completed via RNA-Seq to determine if BROMO differed compared with CON within intestinal epithelium or mesenteric adipose mRNA isolates. Differential expression thresholds were set at a significant P – valueP-value (P < 0.05) and a fold change ≥ 1.5. Only two genes were differentially expressed within the intestinal epithelium but there were 20 differentially expressed genes in the mesenteric adipose tissue (6 up regulated and 14 down regulated). Functions related to cell movement, cell development, cell growth and proliferation, cell death, and overall cellular function and maintenance were the top 5 functional molecular categories influenced by BROMO treatment within the intestinal epithelium. The top molecular categories within mesenteric adipose were antigen presentation, protein synthesis, cell death, cell movement, and cell to cell signaling and interaction. In conclusion, BROMO treatment influenced the intestinal epithelium and mesenteric adipose transcriptome and identified genes and pathways influential to the effects associated with alkaloid exposure which are important to beef production.